The Improvement of Civic Education Instructional Quality Throught Make a Match Model Assisted Picture Card Media - Purnianingrum, Leny Shela (Universitas Sebelas Maret, 2020)
Purpose of research to improve the quality of Civic Education Instructional Quality Throught Make a Match Model Assisted Picture Card Media. Research design used classroom action research, it conducted of three cycles with four stages: planning, running, observing, and reflecting. The techniques data collection used observation, test, documentation, interview and field notes. The techniques of data analized used Qualitative and quantitative descriptive. The research findings showed: (1) the skill of teacher improved in every cycle. In cycle I, the score was 28 with good criteria. In cycle II, the score was 32 with good criteria. In cycle III, the score was 35 with very good criteria, (2) Students activity showed improvement in every cycle. In cycle I, the score was 21,7 with enough criteria In cycle II, the score was 25,13 with good criteria. In cycle III, the score was 28,21 with good criteria, (3) Students learning outcome showed improvement in every cycle with classical comprehension in cycle I 63%, cycle II 76,32%, and cycle III 86,84%. Conclusion of the research is make a match Model Assisted Picture Card Media can improve the quality of civic education instructional.